Therapeutic Potential Of Menstrual Blood-Derived Endometrium Stem Cells On In Vitro And In Vivo Parkinson's Disease Models - Li, Han (2019)
Human menstrual blood-derived endometrial stem cells (MenSCs) have shown therapeutic potential on various diseases by immunoregulation and tissue regeneration. However, their effects on Parkinson’s disease (PD) remain unknown. The aim of this study was to evaluate the protective function of MenSCs and their derivatives on in vitro and in vivo PD models. Neuroblastoma cell line (SH-SY5Y) and mouse midbrain slice were exposed to 1-methyl-4-phenylpyridinium (MPP+) to establish in vitro level PD models. Then, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) was used to construct PD mouse model by intraperitoneal injection. After co-culture in vitro PD models with conditioned medium of MenSCs (MenSCs-CM), the viability of cell and midbrain slice were detected by Prestoblue and lactate dehydrogenase assay. The expression of inflammatory genes, anti-oxidant and apoptosis-related genes were detected by qRT-PCR. Dihydroethidium, Rhodamine123, and Annexin V/PI staining were used to detect reactive oxygen species (ROS), mitochondrial membrane potential, and cell apoptosis, respectively. Protein array was conducted to analyze factors inside MenSCs-CM. Moreover, MenSCs were transplanted to striatum (Str) region of PD mouse brain using a stereotaxic instrument. Survival time of MenSCs, dopamine (DA) level, expression of inflammatory genes and anti-oxidant genes were evaluated. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was used to analyze pathways.